Kingdom of Morocco : Health Policy Note Towards a More Equitable and Sustainable Health Care System - Policy Challenges and Opportunities - World Bank (Washington, DC, 2014)
This note identifies three main issues and proposes a set of short- and longer-term policy measures for each. The publicly financed and run health care system does not meet healthcare needs of the majority of the Moroccans. Only half of the population uses health services when experiencing an illness, indicating that people who live outside big cities either cannot or will not pay for poorer quality services in rural health facilities. While in the short term limited use of healthcare services because of inability or unwillingness to pay may not significantly affect levels of morbidity and mortality resulting from non-communicable diseases, the impact is likely to grow exponentially in the next two decades. Despite recent attempts by the government to expand population coverage, improve system governance, and increase the quality of care, Morocco's health care system remains predominantly state owned and managed, yet highly fragmented. On one hand, the system is not truly pluralistic because of negligible participation of providers and consumers in system governance. On the other hand, the execution of all main healthcare functions are segmented across several government agencies, or applicable to different population segments. In addition, low and poorly allocated public outlays for health care result in inefficiencies in the allocation and use of public resources, as well as in high private out-of-pocket expenditures. If a publicly funded health insurance scheme is intended to provide universal coverage for an essential package of services, a significant restructuring of the existing institutional architecture and of the legislative and regulatory framework will be needed to make it a reality.